Productive Replication of Human Papillomavirus 31 Requires DNA Repair Factor Nbs1 - Anacker, Daniel C. (American Society for Microbiology, 2014)
Activation of the ATM (ataxia telangiectasia-mutated kinase)-dependent DNA damage response (DDR) is necessary for productive replication of human papillomavirus 31 (HPV31). We previously found that DNA repair and homologous recombination (HR) factors localize to sites of HPV replication, suggesting that ATM activity is required to recruit factors to viral genomes that can productively replicate viral DNA in a recombination-dependent manner. The Mre11-Rad50-Nbs1 (MRN) complex is an essential component of the DDR that is necessary for ATM-mediated HR repair and localizes to HPV DNA foci. In this study, we demonstrate that the HPV E7 protein is sufficient to increase levels of the MRN complex and also interacts with MRN components. We have found that Nbs1 depletion blocks productive viral replication and results in decreased localization of Mre11, Rad50, and the principal HR factor Rad51 to HPV DNA foci upon differentiation. Nbs1 contributes to the DDR by acting as an upstream activator of ATM in response to double-strand DNA breaks (DSBs) and as a downstream effector of ATM activity in the intra-S-phase checkpoint. We have found that phosphorylation of ATM and its downstream target Chk2, as well as SMC1 (structural maintenance of chromosome 1), is maintained upon Nbs1 knockdown in differentiating cells. Given that ATM and Chk2 are required for productive replication, our results suggest that Nbs1 contributes to viral replication outside its role as an ATM activator, potentially through ensuring localization of DNA repair factors to viral genomes that are necessary for efficient productive replication. IMPORTANCE The mechanisms that regulate human papillomavirus (HPV) replication during the viral life cycle are not well understood. Our finding that Nbs1 is necessary for productive replication even in the presence of ATM (ataxia telangiectasia-mutated kinase) and Chk2 phosphorylation offers evidence that Nbs1 contributes to viral replication downstream of facilitating ATM activation. Nbs1 is required for the recruitment of Mre11 and Rad50 to viral genomes, suggesting that the MRN complex plays a direct role in facilitating productive viral replication, potentially through the processing of substrates that are recognized by the key homologous recombination (HR) factor Rad51. The discovery that E7 increases levels of MRN components, and MRN complex formation, identifies a novel role for E7 in facilitating productive replication. Our study not only identifies DNA repair factors necessary for HPV replication but also provides a deeper understanding of how HPV utilizes the DNA damage response to regulate viral replication.